Health professionals who have worked in COVID-19 immunization centers suffer the effects of violence - Brunelli, Laura; Scarpis, Enrico; Lo Presti, Tancredi; Fiorillo, Francesca; Campanella, Fabio; Zuliani, Paola; Farneti, Federico; Croci, Eleonora; Pellizzari, Barbara; Cocconi, Roberto; Arnoldo, Luca (Frontiers in Public Health, 2023)
Background The phenomenon violence against health professionals has received increasing attention in recent years because of its frequency and significant impact on victims’ mental health and disruption of health services. Despite this attention, little is known about the incidence of workplace violence in the highly politicized immunization services. Therefore, we decided to examine the prevalence of workplace violence in the COVID-19 immunization campaign, the risk and protective factors, and the impact on victims’ mental health. Methods Between March and April 2022, we conducted an anonymous online survey among health professionals working in COVID-19 vaccination centers in the Friuli-Venezia Giulia Region (Italy). We used the Questionnaire for Workplace Violence in Healthcare Settings and the Impact of Event Scale–Revised. Results Of the 200 participants, 93 (46.5%) reported being victims of an act of violence during the vaccination campaign, 60 of them verbally and 7 physically. In 35.5% of cases, the IES score indicated a possible post-traumatic stress reaction in the victim. Opinions on measures to prevent violence and support workers in the workplace differed according to the sex of the health professional, with women emphasizing the need for self-defense training and improvement of security arrangements (p < 0.001). Conclusion One-third of health professionals involved in the COVID-19 immunization campaign reported that their mental health was affected by workplace violence. Public health professionals dealing with politicized and debated issues such as immunization should receive more attention, as should the implementation of a more structured and multidisciplinary approach to the problem within healthcare organizations.